2021
DOI: 10.3390/en14217388
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Active Power Control for PV-ESS Systems: A Review

Abstract: The penetration of solar energy in the modern power system is still increasing with a fast growth rate after long development due to reduced environmental impact and ever-decreasing photovoltaic panel cost. Meanwhile, distribution networks have to deal with a huge amount and frequent fluctuations of power due to the intermittent nature of solar energy, which influences the grid stability and could cause a voltage rise in the low-voltage grid. In order to reduce these fluctuations and ensure a stable and reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Numerous publications address voltage regulation through active and reactive power with the use of PV or energy storage inverters. Most of them focus on the control strategy, especially if both devices are used [21,[23][24][25][26], control algorithms [20,27,28] and the effects of control in dependence on the network impedance [29]. It is shown that these methods and strategies presented are effective in limiting voltage rises and unbalances.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous publications address voltage regulation through active and reactive power with the use of PV or energy storage inverters. Most of them focus on the control strategy, especially if both devices are used [21,[23][24][25][26], control algorithms [20,27,28] and the effects of control in dependence on the network impedance [29]. It is shown that these methods and strategies presented are effective in limiting voltage rises and unbalances.…”
Section: Introductionmentioning
confidence: 99%
“…PV generators are very well suited to distributed generation in low-voltage grids [4][5][6][7][8]. However, most of the time these kinds of grids require some support in order to meet certain requirements, reduce losses and increase capacity.…”
Section: Introductionmentioning
confidence: 99%